2019
DOI: 10.1038/s41598-019-51274-x
|View full text |Cite
|
Sign up to set email alerts
|

Ecosystem-bedrock interaction changes nutrient compartmentalization during early oxidative weathering

Abstract: Ecosystem-bedrock interactions power the biogeochemical cycles of Earth’s shallow crust, supporting life, stimulating substrate transformation, and spurring evolutionary innovation. While oxidative processes have dominated half of terrestrial history, the relative contribution of the biosphere and its chemical fingerprints on Earth’s developing regolith are still poorly constrained. Here, we report results from a two-year incipient weathering experiment. We found that the mass release and compartmentalization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 42 publications
3
12
0
Order By: Relevance
“…As expected, we found more organic compounds resulting from the metabolization of the leaves in canopy soils than in the forest floor soils, which contain much less organic carbon. This is again consistent with the origin of soil in canopies, which is mostly a result of plant litter, in contrast with the ground soil, which is mostly a result of bedrock weathering and leaching [55].…”
Section: Metabolome Of Forest Floor and Canopy Soilssupporting
confidence: 85%
“…As expected, we found more organic compounds resulting from the metabolization of the leaves in canopy soils than in the forest floor soils, which contain much less organic carbon. This is again consistent with the origin of soil in canopies, which is mostly a result of plant litter, in contrast with the ground soil, which is mostly a result of bedrock weathering and leaching [55].…”
Section: Metabolome Of Forest Floor and Canopy Soilssupporting
confidence: 85%
“…Further, plant root or vegetation systems can produce preferential flow routes in the unsaturation zone, whereas heavy floral cover can lead to decreased surface runoff and high rates of evapotranspiration [53]. Water is a solvent and is capable of dissolving and interacting with organic and inorganic components of soils, minerals (anions or cations), and various types of bedrock [54]. Mineral dissolution is a slow process that takes days, years, or decades and depends on the mineral solubility, and affects many of the qualitative characteristics of aquifers, for example, hardness and pH [55].…”
Section: Geological Factorsmentioning
confidence: 99%
“…Although the large-scale impact of chemical compounds secreted by microbes on silicate weathering rates remains an open and controversial question (e.g. 27 30 ), several studies showed that chemically aggressive conditions (low pH, high concentration of organic acids) can result in a significant increase of silicate weathering rates, at least locally 25 , 31 . Here, an increase of the dissolution rate of chlorite by up to two orders of magnitude would have been required to get an appreciable release of Mn.…”
Section: Discussionmentioning
confidence: 99%